Corporate Governance Research Mapping with Bibliometric - Rikah, Rikah (Jurnal Ekuisci, 2024)
This paper intends to conduct a comprehensive analysis of articles focusing on the field of corporate governance from various studies that have been published in the Scopus database. A bibliometric approach is used to identify common patterns in research related to corporate governance. The research is based on an analysis of 2,202 articles from 2013 to 2022 and indexed in the Scopus database. The findings reveal that research on corporations is still dominated by countries such as the United States, the United Kingdom, and Malaysia. Some keywords such as "political connections, capital structure, board size, institutional ownership, ownership structure, sustainability, and board characteristics" have been frequently used by researchers in recent articles. This bibliometric study provides valuable initial insights into the literature related to corporate governance. This approach helps understand research trends, publishing patterns, and geographic focus that already exist in this domain. In addition, this analysis can guide researchers, practitioners, and other stakeholders in planning and directing research forward. By identifying research gaps and remaining untouched areas, these bibliometric studies can spark the development of further relevant and impactful research.